The car engine of your car is able to propel your car of mass m with a constant power P .
Find the distance traveled ( in meters) by your car in just 9 s e c after beginning from rest at t = 0 .
ASSUMPTIONS:-
P = 1 0 0 k W m = 2 0 0 0 k g
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Excellent solution!!
Very nice question!!!
Assuming that the power is entirely used for kinetic energy, we have K ( t ) = W ( t ) = P ⋅ t = 1 0 5 t where K is the kinetic energy of the car in Joules. From K = 2 1 m v 2 , we have 1 0 5 t = 2 1 ⋅ 2 0 0 0 v 2 ⟹ ∣ v ∣ = 1 0 t . To find the distance travelled from t = 0 to t = 9 , we integrate the speed: Δ x = t = 0 ∫ t = 9 ∣ v ∣ d t = t = 0 ∫ t = 9 1 0 t d t = 1 0 × 2 3 ( 9 2 3 − 0 2 3 ) = 1 8 0 m.
It should be 2/3 in the multiplication
Remember the definition of power, and that the only energy that is being added to our system is kinetic:
P = d t d E = d t d 2 1 m v 2 = 2 1 m 2 v d t d v = m v d t d v
We then rearrange, and solve the differential equation for velocity (remember that power is constant):
m P = v d t d v ⇒ ∫ m P d t = ∫ v d v ⇒ 2 v 2 = m P t ⇒ v ( t ) = m 2 P t
Finally, we integrate with respect to time from 0 to 9 :
d = ∫ 0 9 v ( t ) d t = ∫ 0 9 m 2 P t d t = m 2 P 3 2 t 3 / 2 ∣ ∣ ∣ ∣ 0 9 = 1 8 0 m
f → v p , v → x ′ ( t ) , x ′ ′ ( t ) = m x ′ ( t ) p , x ′ ( 0 ) = 0 , x ( 0 ) = 0 ⇒ x ( t ) → 3 m p 2 2 ( p t ) 3 / 2 , substituting p as 100 kw, m as 2000 kg and t as 9 s and converting to meters: 180 meters.
Of course it's original. I'll mention the source if copied.
Problem Loading...
Note Loading...
Set Loading...
From the definition of Power in Mechanics, we can write the relation that:- P = F v P = m a v Using the relation that a = v d x d v . P = m v d x d v v P d x = m v 2 d x d v Integrating the above expression we get:- ∫ 0 x P d x = ∫ 0 v m v 2 d v P x = 3 m v 3 m 3 P x = v 3 d t d x = ( m 3 P x ) 3 1 x 3 1 d x = ( m 3 P ) 3 1 d t Again integrating both sides we get:- ∫ 0 x x 3 1 d x = ∫ 0 t ( m 3 P ) 3 1 d t 2 3 x 3 2 = ( m 3 P ) 3 1 t Now cubing both sides:- 8 2 7 x 2 = m 3 P m t 3 x 2 = 9 m 8 P t 3 x = 3 2 2 m P t t Now substituting the given values we get x = 1 8 0 m